GERAKAN SAREKAT BURUH SEMARANG TAHUN 1913-1925 - Novita, Angghi (Journal of Indonesian History, 2014)
Semarang is a growing industrial city since colonial era. At that time, Semarang has become traffic of sugar trade that influence to economic and administrative role for the colonial government. The labor in Semarang works in factories, plantations, ports, and railways. They works with minimum wage, so that they are compelled to build union. In 1913 until 1925 is the year of revival Semarang laborâs union. Around the years, laborâs union grew along with the development of communism in this city. Laborâs union in Semarang characterized by a variety of strike action as a resistance by ploretariat to the arbitrariness of the capital. The biggest strike by laborâs union took place in 1923 by Railway Workerâs Union (VSTP) and in 1925 by the Port Workerâs Union (SPPL). The strike is so big, cause followed by thousands even by ten of thousands of workers and the impact was spreading. In 1926 laborâs union in Semarang declined because Communism wich greatly affect the movement of laborâs union has become aware prohibited. Destruction of communism in Semarang make the movement of laborâs union being regressive.